Diversity of Ochrobactrum species in food animals, antibiotic resistance phenotypes and polymorphisms in the blaOCH gene. Issue 17 (18th August 2017) - Alonso, Carla Andrea; Kwabugge, Yakubu A.; Anyanwu, Madubuike U.; Torres, Carmen; Chah, Kennedy F.
Abstract: Twenty-six lactose non-fermenting, oxidase, urease and citrate-positive Gram-negative rods, isolated from broiler chickens, pigs and cattle at slaughter, were subjected to the matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry and 16S rDNA sequencing for identification. Susceptibility to 14 antimicrobials was determined by the disc diffusion method. Ochrobactrum isolates resistant to third-generation cephalosporins were PCR-screened for the presence of the Ochrobactrum anthropi ampC gene ( bla OCH ). A 547-bp internal segment of bla OCH in the Ochrobactrum spp isolates was amplified with a newly designed primer set, and a phylogenetic reconstruction based on the complete amino acid sequence of bla OCH obtained from nine Ochrobactrum strains in our collection and 20 O. anthropi available in the GenBank was undertaken. All the Ochrobactrum isolates were resistant to the expanded-spectrum beta-lactams and streptomycin. None of the isolates was resistant to imipenem while 41.7% to 50.0% of them were resistant to fluoroquinolones. The bla OCH gene was detected in 16 (66.7%) and 20 (83.3%) of the 24 Ochrobactrum isolates ( O. intermedium/O. tritici species), using primers designed for O. anthropi and the newly designed primer set, respectively. Six bla OCH variants grouped into two divergent clusters were identified. This is the first report of the complete nucleotide sequence of the bla OCH gene in non- antropi Ochrobactrum species. Abstract : Food animals (broiler chickens, cattle and pigs) act as reservoirs of multi-resistant Ochrobactrum species showing genetic polymorphisms in the class C beta-lactamase codifying blaOCH gene.